2019
DOI: 10.1155/2019/2871840
|View full text |Cite
|
Sign up to set email alerts
|

Noble Gas Release from Bedded Rock Salt during Deformation

Abstract: Geogenic noble gases are contained in crustal rocks at inter- and intracrystalline sites. In this study, bedded rock salt from southern New Mexico was deformed in a variety of triaxial compression states while measuring the release of naturally contained helium and argon utilizing mass spectrometry. Noble gas release is empirically correlated to volumetric strain and acoustic emissions. At low confining pressures, rock salt deforms primarily by microfracturing, rupturing crystal grains, and releasing helium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…He and 40 Ar release has been shown to be highly sensitive to triaxial deformation [4,5] and show a similar pattern to Rn, with (1) constant or slightly lower gas release during initial compression, (2) increasing gas release after reaching around 1/3 of the ultimate yield stress due to microfracture during compression, and (3) rapidly increasing gas release just before and during macrofracture, subsequently dropping after macrofracture [5,7]. The gas release signal size has been shown to change as a function of rock type and as a result of deformation style [4][5][6]. These noble gas release signals have been used to infer changes in rock flow and transport properties due to fracture creation at the lab scale, using dynamic fracture flow models and matching to 4 He release signals [7].…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…He and 40 Ar release has been shown to be highly sensitive to triaxial deformation [4,5] and show a similar pattern to Rn, with (1) constant or slightly lower gas release during initial compression, (2) increasing gas release after reaching around 1/3 of the ultimate yield stress due to microfracture during compression, and (3) rapidly increasing gas release just before and during macrofracture, subsequently dropping after macrofracture [5,7]. The gas release signal size has been shown to change as a function of rock type and as a result of deformation style [4][5][6]. These noble gas release signals have been used to infer changes in rock flow and transport properties due to fracture creation at the lab scale, using dynamic fracture flow models and matching to 4 He release signals [7].…”
Section: Introductionmentioning
confidence: 74%
“…Thus, it is clear we sampled noble gas composition from several locations that saw significant deformation. In our experience in the lab, radiogenic noble gas release is extremely sensitive to rock deformation across a broad spectrum of rock types and deformation styles [4][5][6][7]. These experiments have shown that when new fractures are being created as a result of deformation, radiogenic noble gases are released in significant quantities.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Groundwater helium is a potential indicator of stress, strain, and seismicity in volcanic systems where subsurface fluid pressure and stress are tightly coupled. Dilation, microfracture, and macroscopic failure break crystal lattices and create new transport pathways to release accumulated radiogenic 4 He into adjacent pore networks and groundwater (Bauer et al, ; Bauer, Gardner, & Lee, ; Bauer, Gardner, & Heath, ). The release of helium due to mechanical deformation during seismic events has been shown to alter helium isotopic composition of groundwater (Brauer et al, ).…”
Section: Introductionmentioning
confidence: 99%